Estado Federal, tributação e autonomia dos entes federados: possibilidade de fortalecimento do federalismo pela centralização - Siqueira, Luiza Noronha (2015)
This dissertation critically reflects about The Brazilian Federal State, the nacional tax system and the political independence of the subdivisions in order to verify the consistency of the federation with respect to political autonomy, administrative and financial of the political subdivisions. Scrutinizes the features of federalism and the federal state, the political subdivisions and competences distributions. Looks after the constitutional limitations on the power to tax discourse upon the competence concerning tax matters, constitutional principles of tax, immunities, and the general rules on tax matters. Addresses the fiscal federalism with references at the cooperative federalism and the loyalty federalism on the financial autonomy and tributary competences of political subdivisions. Considering whether to creation of the Value Added Tax in Brazil and its repercussions in relation to the federal agreement